Acehnese parents’ attitudes and their implications in the intergenerational transmission of the heritage language - Idaryani Idaryani; Fidyati Fidyati (Studies in English Language and Education, 2023)
This study aims to find out the Acehnese parents’ attitudes toward their heritage language, Acehnese, and its implication for the intergenerational transmission of the Acehnese language in the family domain among Acehnese parents residing in two suburbs of Lhokseumawe city in Aceh Province, Indonesia. This qualitative study collected data from semi-structured interviews with 20 female parents who are from endogamy families and Acehnese native speakers. The results of the study underlined three significant issues. First, the parents’ attitudes toward higher educational degree graduates toward their heritage language are negative, and have low self-esteem to speak their heritage language which gradually resulted in a language shift among female parents. However, the parents with lower educational degrees are more confident to speak Acehnese with a strong sense of belonging to their heritage language. Second, a discrepancy is found between the parents’ declaration and their practices in using Acehnese as a mother tongue in their homes because of educational pressures and negative attitudes of the parents. Last, the traditional pattern of intergenerational transmission of Acehnese has been disturbed in the home domains, and this resulted in the Acehnese language being under threat. Consequently, the ability of Acehnese children in speaking Acehnese deteriorates. This study suggests that the important status of Acehnese needs to be recognized as equally important as Indonesian by strengthening the local content policy and immersion approach in schools. Revising the language planning and policy to improve awareness of the values of Acehnese needs to be done.